Polytechnic Student’s Attitude and Their Achievement in the Use of English and Communication Course for Learning - Cyril Abioye Charles Olowoyeye; Gboyega Ayodeji Aladesusi (Indonesian Journal of Multidiciplinary Research, 2022)
This study determined Polytechnic Student’s Attitude and their achievement in the use of English and Communication courses for learning. The study adopted descriptive research of the survey type. The population for this study was made up of all polytechnic students in Ondo-State. Proportional sampling techniques were used to allocate many respondents in each school based on their estimated population using Israel Model. The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of statistical product and service solution (SPSS) version 20.0. The findings indicated that there is no significant relationship between entry qualification of the Polytechnic students and their attitude to the Use of English and Communication Course. No significant relationship between the attitude of Polytechnic students and their achievement in the use of English Courses. The study concluded that Polytechnic students’ entry qualification enhances their attitude toward English and Communication. Therefore, it was recommended that Polytechnic authorities should ensure the provision of infrastructural facilities such as standard 1ibráries well-equipped language laboratories, and modern teaching aids.